ANÁLISE COMPARATIVA DO ENCERRAMENTO DO LIXÃO E TRANSIÇÃO PARA ABERTURA DE ATERRO SANITÁRIO, NO MUNICÍPIO DE SIDROLÂNDIA – MS - Secco, Anderson; Hananda, Isabella; Sovernigo, Thayza; Brumatti, Amanda; Fachin, Elioterio (ANAIS DO ENIC, 2018)
-